Análisis de Factores Sociofamiliares Influyentes en la delincuencia Juvenil en el Municipio de Uribia -La Guajira. (2023)
This research aimed to analyze the socio-family factors that influence juvenile delinquency in the Municipality of Uribia, La Guajira. To achieve this, a methodology was employed under a descriptive research type with an empirical quantitative approach, using a non-experimental and cross-sectional field design. The research included the administration of a questionnaire to 47 adolescents aged 12 to 17, focusing on three dimensions: Family Typology, Family Environment, and Strategies to minimize delinquency.